Characterization of Pectinase Enzyme Produced from Indigenous Yeast Isolates During Fermentation of Robusta Coffee Beans - Fitri, Hasanul; Yanto, Subari; Putra, Reski Praja (PT FORMOSA CENDEKIA GLOBAL, 2024)
The following research aims to understand indigenous yeast isolates that are pectinolytic, the effect of incubation time on pectinase enzyme activity, and the pH and temperature properties of pectinase enzymes obtained from indigenous yeasts from spontaneous fermentation of robusta coffee beans. The following type of research is an experiment through RAL (Completely Randomized Design). The results showed that testing of seven indigenous yeast isolates was pectinolytic and that the highest pectinolytic ability was isolate K24I7 with a clear zone diameter of 3.13 mm. The characterization results of the pectinase enzyme produced from isolate K24I7 were optimum at pH 5.5 with an enzyme specific activity value of 10.09 U/mg and optimum temperature in the range of 40oC-60oC with an average enzyme specific activity of 10.08 U/mg. The pectinase enzyme produced from isolate K24I7 is thermophile because it is still active at 70°C